Association between metabolically healthy obesity and carotid intima-media thickness in Korean adolescents with overweight and obesity - Sohyun Shin; Hwa Young Kim; Joowon Lee; Young Jin Ryu; Ji Young Kim; Jaehyun Kim (Korean Society of Pediatric Endocrinology, 2024)
Purpose Data regarding the association between metabolically healthy obesity (MHO) and preclinical atherosclerosis in childhood are lacking. Carotid intima-media thickness (cIMT) is a noninvasive method used to assess cardiovascular risk. This study examined the relationships among cIMT, metabolic phenotypes, and cardiometabolic risk factors (CMRFs) in overweight and obese adolescents. Methods Anthropometric, biochemical, and cIMT data were collected. The study participants were categorized as MHO or metabolically unhealthy obesity (MUO) based on insulin resistance. CMRFs were assessed using blood pressure (BP); levels of triglycerides, high-density lipoprotein cholesterol (HDL-C), and fasting plasma glucose; or a diagnosis of diabetes mellitus. Differences in cIMT values were evaluated according to the metabolic phenotype and factors associated with cIMT. Results Among the 111 participants (80 boys, 72.1%), 23 (20.7%) were classified as MHO and 88 (79.3%) as MUO. The MHO group exhibited lower glycated hemoglobin and triglyceride levels and higher HDL-C levels compared to those exhibited by the MUO group (all P<0.01). The cIMT values did not differ significantly between the MHO and MUO groups. The high cIMT tertile group revealed higher systolic BP compared to that exhibited by the low cIMT tertile group (123.7±2.1 mmHg vs. 116.9±1.6 mmHg, P=0.028). Mean cIMT was positively correlated with age (β=0.009) and body mass index (BMI) (β=0.033) after adjusting for covariates (both P<0.05). Conclusions In overweight and obese Korean adolescents, cIMT was associated with age and BMI but not with metabolic phenotype or CMRFs. Further research is warranted to determine the relationship between cIMT during adolescence and cardiovascular outcomes during adulthood.